Tax Policy with Uncertain Future Costs: Some Simple Models - Christopher Ball; John Creedy (New Zealand Government, The Treasury, 2013)
This paper considers the extent to which the standard argument, that the disproportionate excess burden of taxation suggests the use of tax-smoothing in the face of future cost increases, is modified by uncertainty regarding the future. The role of uncertainty and risk aversion are examined using several highly simplified models involving a possible future contingency requiring an increase in tax-financed expenditure.
Keywords: H20; D81; D90; 330; Tax Smoothing; Uncertainty; Risk Aversion; Excess Burden; Steuerpolitik; Entscheidung unter Unsicherheit; Risikoaversion; Intertemporale Entscheidung; Excess Burden; Optimale Besteuerung; Theorie